STRUCTURE OF ARABIC a workbook in the ten measures. - DiMeo, David Fred.; Hassan, Inas. ([S.l.] : ROUTLEDGE, 2024)
The Structure of Arabic: A Workbook in the Ten Measures is a comprehensive guide and workbook inthe ten measures of Arabic words, the backbone of the Arabic lexical system, and provides a systematic explanation of the root and pattern system that forms the basis of most Arabic words. Successful Arabic learners have long recognized mastery of these measures and patterns as key to understanding the Arabic language. With knowledge of this system, learners will be able to predict the meaning of unfamiliar words, recognize the function of words, and understand correct pronunciation of Arabic words, making vocabulary acquisition and retention easier. This unique textbook introduces measures and patterns sequentially across ten chapters, helping learners to navigate the topics in a logical manner. Without complicated jargon or technical language, this easy-to-understand textbook demystifies key topics in Arabic grammar. Comparative sentences which encapsulate the differences between measures give context, and exercises within the chapters serve to consolidate the learners' grasp of the material presented. Designed to supplement both class-based Arabic courses and independent study, The Structure of Arabic will help learners of Arabic at all levels of competency to improve their vocabulary, pronunciation, spelling, and comprehension.
Keywords: Arabic language -- Morphology; FOREIGN LANGUAGE STUDY / Arabic; LANGUAGE ARTS & DISCIPLINES / Grammar